Discretionary Collaborative Behaviour (Dcb) Of Students From Institutes Of Higher Learning In Malaysia - Huam, Hon Tat; Jantan, Muhamad; Mohd. Noor, Mohd. Nasser (Asian Academy of Management (AAM), 2008)
It is generally accepted that a graduate who is satisfied with the quality of his or her educational experience is likely to reciprocate by performing certain behaviours that benefit the alma mater. Whether or not this reciprocating behaviour is consistent across all individuals, however, is much less clear. The present study addresses this question using the Satisfaction with Life Scale (SWLS) to measure life satisfaction. Three components of intended discretionary collaborative behaviours (IDCB) – institutional support, word-of-mouth, and financial contributions –were extracted from factor analysis. Using data from 167 usable responses to a mail and e-mail survey of 1,500 MBA graduates, we find that for low levels of life satisfaction, the impact of overall student satisfaction (OSS) on the components of IDCB was either negligible or negative. However, for high levels of life satisfaction, the impact was generally in a positive direction, and a moderate level of OSS was already sufficient for the graduates to perform intended discretionary services in terms of word-of-mouth and financial contributions. Taken together, the outcomes of this study may offer preliminary support that, even though the occurrence of student dissatisfaction with overall services is known to reduce the likelihood of IDCBs, it is possible that high levels of life satisfaction may serve as support against the non-performance of IDCBs.